The effect and safety of sleep interventions on suicidal thoughts and behavior – A systematic review and meta-analyses - Paula von Spreckelsen; Daan Schouten; Natasha G. Waslam; Patricia Katuin; Henriette D. Heering; Caroline Planting; Niki Antypa; Liia Kivelä; Marike Lancel; Lizanne J.S. Schweren (Sleep Medicine: X)
Background: Sleep disturbances are a risk factor for suicidal ideation, suicide attempts and suicide. While recent findings suggest that improving sleep by psychotherapeutic sleep interventions exerts a positive effect on suicidality, there are also indications that certain sleep medications are associated with an increased risk for suicidality. Given these discrepancies, the current study systematically reviewed the effect of non-pharmacological and pharmacological sleep interventions on suicidality. Methods: A systematic literature search of various scientific databases was conducted (March 2025). Randomized controlled trials that examined the effect of sleep interventions on suicidality were searched for. Results: The search strategy resulted in 5037 unique articles. A total of k = 44 articles (N = 14965 participants) were included in the systematic review. The results indicate that sleep interventions, particularly psychotherapeutic sleep treatments (g = −0.17, [-0.26 to −0.08]), result in a small significant reduction of suicidal ideation. No conclusive evidence was found for the effect or safety of pharmacotherapy or light therapy targeting sleep disturbance on suicidality. The findings should be interpreted in light of the limited number of studies with often small sample sizes, methodological inconsistencies in monitoring suicidality as an adverse event, restrictions on the inclusion of people with suicidality, and reliance on suicidal ideation as an outcome measure of suicidality. Conclusion: Health care professionals are recommended to apply psychotherapeutic sleep interventions, such as cognitive behavioral therapy for insomnia, to reduce suicidal ideation in clients with disturbed sleep. When prescribing medications for disturbed sleep, we recommend professionals to closely monitor clients for potential adverse effects on suicidality.